MgFe-LDH and MgFe-LDH-Derived Mixed Oxides as Effective Amoxicillin Adsorbents: A Comparison Study - Purwajanti, Swasmi; Amaratirta, Jasmine Cupid; Izzati, Razita Najla; Rohmah, Nur; Zulfi, Akmal; Rezeki, Yulianto Agung; Patah, Aep (Trends in Sciences, 2026)
Antibiotic contamination, particularly from amoxicillin, poses serious ecological and health risks due to its persistence in aquatic systems. This study hypothesized that MgFe-layered double hydroxide (MgFe-LDH) synthesized from salt-industry by-product (bittern) and its calcined derivative (MgFe-CLDH) can act as sustainable and efficient adsorbents for amoxicillin removal. MgFe-LDH was prepared via co-precipitation and partially calcined at 450 °C to form MgFe-CLDH. Both materials were characterized by XRD, SEM, FTIR, and BET analyses, and their adsorption behaviors were evaluated under varying pH, contact time, initial concentration, and co-existing ions. MgFe-LDH and MgFe-CLDH exhibited maximum adsorption capacities of 82.79 and 86.94 mg/g, respectively. Kinetic studies showed that MgFe-LDH followed a pseudo-second-order model (chemisorption), whereas MgFe-CLDH followed a pseudo-first-order model (physisorption). Freundlich isotherm fitting indicated multilayer adsorption on heterogeneous surfaces. Regeneration tests confirmed stable reusability, with optimal performance observed after the second adsorption cycle. These findings validate the hypothesis and demonstrate that MgFe-based LDH adsorbents derived from industrial by-products offer a cost-effective route for antibiotic wastewater remediation. HIGHLIGHTS Sustainable MgFe-LDH synthesized from salt industry by-product (bittern). Calcined MgFe-CLDH showed enhanced adsorption via memory effect. High adsorption capacities: 82.79 mg/g (LDH) and 86.94 mg/g (CLDH). Distinct kinetics: LDH fits pseudo-second-order, CLDH fits pseudo-first-order. Freundlich isotherm confirmed multilayer adsorption with good reusability. GRAPHICAL ABSTRACT